Peran Tata kelola Perusahaan dan Karakteristik Perusahaan Dalam Mencegah Kecurangan Laporan Keuangan - Carmen Angela Christabel Apfel; Stefani Lily Indarto (Universitas Katolik Soegijapranata Semarang, 2026)
This study examines the influence of managerial ownership, Board of Commissioners independence, and auditor quality on fraudulent financial reports. As many as 2,432 firm-observations are selected from Indonesian Capital Market in the period of 2022 to 2024. Results suggest that managerial ownership and the percentage of receivables have positive effects on financial report fraud. However, leverage, Board of Commissioners independence, and auditor quality have no effects on fraudulent financial reports. These findings highlight the importance of limiting stock ownership by directors to prevent managers from misusing company resources for personal gain rather than shareholder interests. Additionally, investors should be wary of significant changes in receivables, which may signal misuse of company resources or unhealthy business practices.